Neuro-Linguistic Programming (NLP) in the Perspectives of Philosophy, Neuroscience, Neuro-Psychology, and Tasawuf - Muhamad Atamimi; Muhtar Solihin (Jurnal Iman dan Spiritualitas, 2026)
This study critically examines Neuro-Linguistic Programming (NLP) through the combined lenses of philosophy and modern neuroscience. It aims to investigate how NLP conceptualizes the relationship between mind, language, and embodied experience, and to what extent its theoretical foundations align with contemporary understandings of consciousness. Employing a qualitative, library-based methodology using conceptual analysis, hermeneutics, and comparative neurocognitive review, this study analyzes primary NLP formulations by Bandler and Grinder alongside philosophical perspectives from Wittgenstein, Merleau-Ponty, and Gadamer, as well as neuroscientific findings on neuroplasticity, mirror neurons, and predictive processing. The findings reveal that NLP provides a constructivist model of consciousness in which meaning, perception, and behavior emerge from the dynamic interaction of neural processes, linguistic structures, and subjective experience. However, its scientific validity remains limited due to the scarcity of consistent empirical evidence, and several NLP techniques rely heavily on anecdotal claims. The study also finds that NLP’s theoretical framework tends to simplify complex ontological questions about consciousness, indicating the need for deeper engagement with phenomenology and neurophilosophy. A major limitation of this research lies in its reliance on textual analysis without empirical examination of NLP practices in therapeutic or cultural settings. Practically, the study recommends a more rigorous integration of NLP with contemporary neuroscience and ethical guidelines to prevent misuse in interpersonal communication, therapy, and political persuasion. Contribution: This research contributes to the philosophy of mind by proposing a synthesis of NLP with neuroscience and phenomenology, presenting it as a Neuro-Linguistic-Phenomenological Programming framework. Practically, it offers a conceptual foundation for the responsible application of NLP in education, communication, and religious or spiritual studies, emphasizing ethical awareness and evidence-based practice.